Associations of the T329S Polymorphism in Flavin-Containing Monooxygenase 3 With Atherosclerosis and Fatty Liver Syndrome in 90-Week-Old Hens - Song, Jianlou; Shi, Xuefeng; Li, Xianyu; Liang, Qianni; Zeng, Lingsen; Li, Guangqi; Yan, Yiyuan; Xu, Guiyun; Zheng, Jiangxia (Frontiers in Veterinary Science, 2022)
This study aimed to evaluate the effects of the spontaneous genetic mutation T329S in flavin-containing monooxygenase 3 (FMO3) on atherosclerosis (AS), fatty liver syndrome (FLS), and adiposity in 90-week-old layers. At 90 weeks of age, 27 FMO3 genotyped Rhode Island White chickens (consisting of nine AA hens, nine AT hens, and nine TT hens) with normal laying performance were selected. The AS lesions, incidence of FLS, fat deposition, metabolic characteristics, and production performance of these egg-layers with different FMO3 genotypes were assessed. The T329S mutation in TT hens reduced the AS lesions (P < 0.01) and altered the plasma metabolic indices more than it did in the AA and AT hens. Furthermore, it reduced the incidence of FLS, hepatic triglyceride deposition (P < 0.05), liver indices (P < 0.05), and fat deposition (P < 0.05) in the subcutis and abdomen of TT hens compared to those of AA and AT hens. Moreover, as an effect of T329S, TT hens laid a higher than average number of eggs and maintained a higher egg-laying rate from 68 to 90 weeks than AA and AT hens. Our study confirmed that the T329S mutation in FMO3 could reduce the development of AS lesions, the incidence of FLS, and fat deposition, which are associated with changes in plasma and hepatic metabolic indices and improvements in the laying performance of older layers. Our results may provide a new strategy for using the T329S mutation to improve the health status and production performance of layers during the late laying period.